Effect of Entrepreneurship Eduaction and Entrepreneurial Characters Toward Entrepreneurial Intention with Business Motivation as Intervening - Phutry Lelliezzia; Al Musadeq; Prasetya Arik (Sekolah Pascasarjana Universitas Brawijaya, 2020)
This study aims to determine the effect of entrepreneurship education and entrepreneur characters to the entrepreneurial intention, in addition, it is also aimed to understand the role of business motivation as a mediator in this study. Population of this study consists of college students from Department of Business Administration, Faculty of Administrative Sciences, Brawijaya University, Malang, East Java, with a sample of 66 respondents. Sampling techniques was using proportional simple random technique. This study uses Path analysis techniques. Results of this study indicate that entrepreneurship education has significant effect toward entrepreneur characters and entrepreneurial intentions. Entrepreneurship education also has direct and indirect influence through business motivation as its intervening variable.